Culture-Related and Individual Differences in Regional Brain Volumes: A Cross-Cultural Voxel-Based Morphometry Study - Huang, Chih-Mao; Doole, Robert; Wu, Changwei W.; Huang, Hsu-Wen; Chao, Yi-Ping (Frontiers in Human Neuroscience, 2019)
Converging behavioral and functional neuroimaging evidence indicates that East Asian and Western individuals have different orientations for processing information that may stem from contrasting cultural values. In this cross-cultural magnetic resonance imaging (MRI) study, we used voxel-based morphometry (VBM) approach to investigate culture-related and individual differences of independent-interdependent orientation in structural brain volume between 57 Taiwanese and 56 Western participants. Each participant’s degree of endorsement of independent and interdependent cultural value was assessed by their self-report on the Singelis Self-construal Scale (SCS). Behaviorally, Taiwanese rated higher SCS scores than Westerners in interdependent value and Westerners rated higher SCS scores than Taiwanese in independent value. The VBM results demonstrated that Western participants showed greater gray matter volume in the fronto-parietal network, whereas Taiwanese participants showed greater regional volume in temporal and occipital regions. Our findings provide supportive evidence that socio-cultural experiences of learned independent-interdependent orientations may play a role in regional brain volumes. However, strategic differences in cognition, genetic variation, and/or modulations of other environmental factors should also be considered to interpret such culture-related effects and potential individual differences.